2021
DOI: 10.3389/fnhum.2021.615584
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Differences in Strategy in the Hand Mental Rotation Task

Abstract: Mental imagery of movement is a potentially valuable rehabilitation task, but its therapeutic efficacy may depend on the specific cognitive strategy employed. Individuals use two main strategies to perform the hand mental rotation task (HMRT), which involves determining whether a visual image depicts a left or right hand. One is the motor imagery (MI) strategy, which involves mentally simulating one’s own hand movements. In this case, task performance as measured by response time (RT) is subject to a medial–la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 34 publications
2
11
0
Order By: Relevance
“…The difference in results for back and palm stimuli in the HLT echo previous findings in healthy young participants (e.g., Brady et al, 2011;Ter Horst et al, 2010), suggesting that visual and kinaesthetic strategies may be differentially recruited in laterality judgements for the different surfaces of the hand, while also indicating that these may differ in susceptibility to impairment in ageing and neurodegeneration. It has been proposed that judging laterality from the back of the hand relies more on visual processes, while the palm is more likely to evoke covert motor simulation (Conson et al, 2020;Nagashima et al, 2021). With explicit measures of MI, in which participants rate the vividness of their imagery in different modalities, older adults have shown a reduction in dominance of visual over kinaesthetic imagery compared with younger adults (Malouin et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The difference in results for back and palm stimuli in the HLT echo previous findings in healthy young participants (e.g., Brady et al, 2011;Ter Horst et al, 2010), suggesting that visual and kinaesthetic strategies may be differentially recruited in laterality judgements for the different surfaces of the hand, while also indicating that these may differ in susceptibility to impairment in ageing and neurodegeneration. It has been proposed that judging laterality from the back of the hand relies more on visual processes, while the palm is more likely to evoke covert motor simulation (Conson et al, 2020;Nagashima et al, 2021). With explicit measures of MI, in which participants rate the vividness of their imagery in different modalities, older adults have shown a reduction in dominance of visual over kinaesthetic imagery compared with younger adults (Malouin et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Hand laterality judgement has been found to be slowed in older adults (Devlin & Wilson, 2010;Saimpont et al, 2009;Wang et al, 2019), in particular for lateral rotations (De Simone et al, 2013;Saimpont et al, 2009), and for the non-dominant side (Saimpont et al, 2009). Older adults have also exhibited less of a clear distinction in performance between back and palm views of the hand (Nagashima et al, 2021): while younger adults consistently showed an effect of biomechanical constraints for the palm only, older adults showed more variability, with some exhibiting a mediallateral difference for the back view. The authors interpreted this as indicating a "motor imagery" strategy as opposed to the "visual imagery" strategy typically assumed for this view.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Differences in HLT performance are also found according to whether stimuli depict the back or palm view of the hand. Typically, participants are slower to recognise images of the palm, and exhibit stronger biomechanical constraint effects for this view (Brady et al 2011 ; de Simone et al 2013 ; Nagashima et al 2021 ; Ter Horst et al 2010 ; Zapparoli et al 2014 ). Although this may in part reflect the greater physical difficulty in rotating one’s own hands with the palm facing up (Conson et al 2020 ), it has also been suggested that viewing the different surfaces of the hand may evoke different strategies, whereby kinesthetic MI is more likely to be involved in judging palm stimuli, while a more visual strategy may be engaged by the back view (Conson et al 2020 ; Nagashima et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Typically, participants are slower to recognise images of the palm, and exhibit stronger biomechanical constraint effects for this view (Brady et al 2011 ; de Simone et al 2013 ; Nagashima et al 2021 ; Ter Horst et al 2010 ; Zapparoli et al 2014 ). Although this may in part reflect the greater physical difficulty in rotating one’s own hands with the palm facing up (Conson et al 2020 ), it has also been suggested that viewing the different surfaces of the hand may evoke different strategies, whereby kinesthetic MI is more likely to be involved in judging palm stimuli, while a more visual strategy may be engaged by the back view (Conson et al 2020 ; Nagashima et al 2021 ). Visual and sensorimotor familiarity may contribute to the back/palm difference, since one’s own hands are more frequently viewed from the back, while the palm may evoke stronger kinesthetic imagery due to its involvement in manual actions (Bläsing et al 2013 ; Conson et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%